Water quality in rural Greenland - acceptability and safety - Judith Y.A. Maréchal; Lisbeth Truelstrup Hansen; Pernille Erland Jensen (Elsevier, 2023)
The low proportion of households with piped drinking water in Greenlandic settlements - and elsewhere in the Arctic, leads to improvised methods of household water storage and water saving practices that could present a risk for public health.This interview-based study investigated the perceptions of safety and acceptability of the water supply in rural Greenlandic households. The bacterial quality of the water distributed by the public supply before and after storage in the homes, of alternative water sourced from nature by the users themselves, and of shared handwash basins used in un-piped homes, was analyzed.The treated water distributed by the rural Greenlandic water supply was acceptable to most users, although half of them expressed concerns about its quality, and distrusted the state of the infrastructure delivering piped water. For drinking, most respondents preferred untreated water from nature, but a majority used mainly piped water for practical reasons of access. The microbial quality of the public water supply met legislative requirements in most cases, but was found to deteriorate during both distribution to some taps, and storage in the homes, which constitutes a challenge to the reliable provision of safe water to users. Water from alternative sources showed slightly higher heterotrophic plate counts (HPC) than piped water, but no Escherichia coli. As for washbasins, they were found to have high levels of contamination in all three bacterial parameters investigated (HPC, coliforms and E. coli), indicating a possible transmission route for pathogens.In conclusion, while the quality of treated water was overall good at distribution, the water saving and storage practices developed to compensate for the lack of piping may threaten public health. Alternative water sources are culturally important and trusted by users, although the possible impact of changes in climate and land use on the reliability of their quality is unknown.